2014
DOI: 10.1590/s1679-78252014001100002
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of combined effects of fibers and nanosilica on the mechanical properties of self-compacting concrete using artificial neural network

Abstract: In this research, the combined effect of nano-silica particles and three fiber types (steel, polypropylene and glass) on the mechanical properties (compressive, tensile and flexural strength) of reinforced self-compacting concrete(SCC) is evaluated. For this purpose, 70 mixtures in A, B, C, D, E, F and G series representing 0, 1, 2, 3, 4, 5 and 6 percent of nano-silica particles in replacing cement content are cast. Each series involves three different fiber types and content; 0.2, 0.3 and 0.5% volume for stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In the study of Tavakoli et al (2014) [61], they have predicted the combined effects of nano-silica particles (0 to 6% replacement of cement content) and three fiber types (steel, polypropylene and glass) on the mechanical properties (compressive, tensile and flexural strength) of reinforced selfcompacting concrete (SCC) using ANN. The experimental data was used to train ANN, and two input variables (percentage of nano particles and fiber) and three outputs (flexural tensile strength, tensile strength behavior and compressive strength) were used.…”
Section: Ann Prediction and Modeling Studiesmentioning
confidence: 99%
“…In the study of Tavakoli et al (2014) [61], they have predicted the combined effects of nano-silica particles (0 to 6% replacement of cement content) and three fiber types (steel, polypropylene and glass) on the mechanical properties (compressive, tensile and flexural strength) of reinforced selfcompacting concrete (SCC) using ANN. The experimental data was used to train ANN, and two input variables (percentage of nano particles and fiber) and three outputs (flexural tensile strength, tensile strength behavior and compressive strength) were used.…”
Section: Ann Prediction and Modeling Studiesmentioning
confidence: 99%
“…Similarly, Kim, H. et al [19], Rusch, S et al [20], and Lo Monte et al [21] have concluded that the BS EN 1992-1-1-2004 [22] code is effective in estimating shrinkage for normally vibrated concrete, while Savija, B et al [23], Rao, A. S. et al [24], and Lee, Y. J. et al [25] have shown the same for VMA type SCC. Tavakoli, M et al [26], Zhou, J et al [27], and Tavakoli, M et al [28] have concluded that IS 1343:2012 [29] code is effective in estimating shrinkage for normally vibrated concrete. Similarly, Sivakumar, A et al [30], Gaur, D. R et al [31], Priyanka, P et al [32], and Singh, B [33] have demonstrated that IS 1343:2012 code is effective in predicting shrinkage for VMA type SCC.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tavakoli et al [10] have predicted the energy absorption capability of fiberreinforced self-compacting concrete which contains nanosilica particles via an MLP-(multilayer perceptron-) type artificial neural network. Tavakoli et al [11] simultaneously researched the mechanical properties of self-compacting concrete with nanosilica particles and various fibers via the MLP artificial neural network. In addition to that, many scholars utilized the ANN for concrete compressive strength prediction.…”
Section: Introductionmentioning
confidence: 99%